IMPACT OF ADDING RUBBER STRIPS TO REEL AND SOME INDICATORS ON THE PERFORMANCE OF JOHN DEERE COMBINE HARVESTER 1450 CWS - Yousif Hilal; Saleh Al-Slevani; Othman Tofeq (Mesopotamia Journal of Agriculture)
There is an increasing interest in developing combine harvesters due to the excessive losses and costs of wheat harvesting. Modifying a new concept can promote the mechanized process for wheat combine harvesters. Therefore, the research aims to examine new modifications in John Deere 1450 CWS combine harvester reel to suit reaping winter wheat under drought and study the effect of the harvester setting parameters on efficiency, percentage of header losses (PHL), total loss percentage (TL), and total harvest loss percentage (THL). A randomized complete block design is used to analyze a factorial experiment with split–split plot and Duncan's test to assess the significant influence of reel modification, reel rotational speed, and harvester forward speed on PHL, THL, TL, and efficiency. The performance of the modification was tested in terms of losses, and the results confirmed the efficiency of the modified reel for wheat harvesting. Furthermore, the results showed that the use of the rubber strips provided the lowest PHL (9.30%), THL (12.57 %), and TL (14.12 %) values with an increase in efficiency performance indicators with counts of 84.46 %. Moreover, PHL, THL, and TL had risen from 5.79 to 17.44%, 7.23 to 20.56%, and 8.59 to 22.15 % for increasing the reel rotational speed from 30 to 60 rpm. Finally, Efficiency indicators recorded the highest significant loss with increased harvester forward speed. The superiority of the forward speed of 5.2 km.hr-1, with the lowest PHL, THL, and TL values over the forward speed of 6.2 km.hr-1.